Endobronhialni ultrazvok z upogljivim bronhoskopom - Terčelj-Zorman, Marjeta (Zdravniški vestnik, 2002)
Background. Conventional imaging procedures proved to be insufficient for staging of lung cancer especially with respect to N-stage, infiltration of mediastinal structures, as well as detection of early lung cancer. Endobronchial ultrasonography (EUS) is an improvement on diagnostic endoscopy.We have been performing EUS with a thin probe inserted through the flexible bronchoscope since 1999 and have obtained good images. EUS proved to be useful in determination of depth of tumor invasion of the bronchial wall; visualization of hilar tumors and their relation to pulmonary vessels; findingperibronchial lymph nodes; determination of the depth of tumor invasionan important finding for terapeutic decisions. Patients and methods. Between March 1999 and September 2001 45 for bronchoscopy and EUS. We used Olympus probes of 20 MHz (UM - 2R/3R, diving unit MH-240 and processor EU-M20 and 30). Results. In 45 patients we used of these, 18 (40%) weref emale and 27(60%) were male. The mean time for EUS was 3-IS.S min. Side effect were negligible. 15 patients needed supplementary oxygen 3 O2 L/min during the examination, the others tolerated it well. Conclusions. EUS is a new technology, usefull and well tolerated. It improves the results of bronchoscopy.
Keywords: Bronchoscopy; Bronhoskopija; Diagnosis; Lung neoplasms; Methods; Pljučne novotvorbe; Ultrasonography